Results of a Fertilization Experiment Performed with Sulphur on Rape Seed Plants - Zsombikné Puy, Katalin; Borbély, Jánosné; Győri, Zoltán (Acta Agraria Debreceniensis, 2004)
The sulphur fertilizing experiment was introduced in the cropping year of 2001/2002, with winter rapeseed. The experiment was performed on a farm in Magyarhomorog, Hajdú-Bihar County. By selecting the location for the experiment, we had to consider the effect of the hard winter that was very unfavourable for rapeseed production, as there was serious frost damage on the sown area previously used for the experiment. In the arable land experiment, results of three different doses of treatment were compared in two replicates, on meadow soil. FitoHorm 32 S solution was used as a sulphur fertilizer, in doses of 3, 6 and 10 l/ha. Evaluating the results, we tried to find a correlation between the amount of fertilizer and the amount of seed-crop or the oil content of the seed. The nitrogen and sulphur contents of the samples were determined using classical methods and an Elementar VarioMax analyser. By this way, it was possible to examine not only the role of Sulphur in rapeseed production, but also to compare and evaluate results obtained by Kjeldahl and the modern, environmentally-friendly combustion method.